Pendampingan Partisipatif dalam Pembinaan Karakter Islami Anak melalui Taman Pendidikan Al-Qur’an (TPA) di Desa Margo Koyo Kecamatan Belitang Jaya Kabupaten OKU Timur - Ahmadi Ahmadi; Qoniatul Rofiah; Rina Anggraini; Laila Nikmatul Hasanah; Selvi Wulandari; Dani Kristanto (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2025)
This community service activity aims to strengthen the development of children’s Islamic character through participatory mentoring in Taman Pendidikan Al-Qur’an (TPA) activities in Margokoyo Village, Belitang Jaya District, OKU Timur Regency. As a non-formal Islamic educational institution, TPA plays a strategic role in reinforcing the values of Islamic Religious Education, particularly in the aspects of faith (aqidah), worship (ibadah), and morality (akhlaq). However, preliminary observations revealed that TPA learning activities remain primarily oriented toward the technical ability to read the Qur’an and have not been systematically integrated with Islamic character development. The community service program was implemented using a participatory mentoring approach involving TPA teachers, students, parents, and community leaders. The implementation methods consisted of planning, implementation, and evaluation stages, focusing on character-based Qur’anic learning assistance, habituation of daily religious practices, strengthening moral values through role modeling and educational storytelling, and enhancing the pedagogical capacity of TPA teachers. The results of the program indicate an improvement in students’ religious understanding, positive behavioral changes reflected in increased discipline, politeness, and religiosity, as well as heightened motivation to participate in TPA activities. In addition, TPA teachers demonstrated improved competence in integrating Islamic character values into Qur’anic learning. These findings confirm that structured and contextual participatory mentoring is effective in strengthening the role of TPA as a community-based institution for fostering children’s Islamic character grounded in Islamic Religious Education.